Composite material pipeline capable of preventing hydrogen leakage
By adopting multi-layer composite pipe design, the problems of hydrogen embrittlement and leakage of traditional materials in high-pressure hydrogen environment are solved, and efficient hydrogen isolation, high temperature resistance and corrosion resistance are achieved, meeting the needs of long-distance transportation and high temperature and high pressure.
Patent Information
- Application Number
- CN202510065513.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Traditional carbon steel and plastic materials are prone to hydrogen embrittlement and leakage in high-pressure hydrogen environments, and it is difficult to meet the requirements of long-distance transportation and high temperature and high pressure.
The multi-layer composite pipe design is adopted, including inner pipe layer, composite gas barrier layer, high-temperature copolymer layer, reinforcement layer and corrosion-resistant polymer protective layer. The gas of the pipe is improved through coextrusion structure and multi-layer interwoven fiber structure. Tightness, high temperature resistance and corrosion resistance.
Effectively prevent hydrogen leakage, improve pipeline strength and high temperature resistance, reduce hydrogen embrittlement and corrosion risks, improve flexibility and operability, reduce weight and material costs, and extend service life.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparing hydrogen transportation pipelines, and in particular to a composite material pipeline for preventing hydrogen leakage. Background Art
[0002] As the importance of hydrogen as a clean energy source continues to increase, the production, storage, transportation and use technologies of hydrogen are developing rapidly. The pipeline system for transporting hydrogen is a key link in the hydrogen industry chain. At present, most pure hydrogen pipelines are made of steel. However, steel is prone to hydrogen embrittlement in a high-pressure hydrogen environment, that is, hydrogen molecules are decomposed into hydrogen atoms and penetrate into the steel, causing the material's performance to degrade and become brittle, which may eventually lead to cracks and failure of the pipeline. Therefore, traditional carbon steel materials have serious safety hazards in hydrogen pipelines.
[0003] In order to overcome this problem, alloy steel materials are used to improve the hydrogen embrittlement resistance of pipelines. However, the cost of alloy steel is high, and due to the lack of flexibility of steel, it is difficult to manufacture it into coils suitable for long-distance transportation and laying. In addition, steel pipes still require additional anti-corrosion coatings, which increases the laying and maintenance costs of pipelines, and the construction process is complicated and time-consuming.
[0004] On the other hand, some low-pressure hydrogen transportation occasions have begun to use plastic materials such as polyethylene or polyvinyl chloride as alternative materials. These plastic materials are resistant to hydrogen embrittlement and corrosion, but under high pressure and high temperature environments, the strength and temperature resistance of plastic materials are poor, making it difficult to meet the requirements of high-pressure hydrogen transportation, and they are prone to leakage due to the penetration of high-pressure hydrogen. This limits their application in high-pressure hydrogen pipelines. Therefore, how to develop a composite pipeline that can solve the problem of hydrogen leakage while having good strength, high temperature resistance and corrosion resistance is an urgent problem to be solved. Summary of the invention
[0005] The purpose of the present invention is to solve the above problems in the prior art and to provide a composite material pipeline for preventing hydrogen leakage.
[0006] The object of the present invention can be achieved by the following technical scheme: a composite material pipeline for preventing hydrogen leakage, characterized in that the composite material pipeline comprises an inner tube layer, a composite gas barrier layer located on the outer surface of the inner tube layer, a high temperature resistant copolymer layer located on the outer surface of the composite gas barrier layer, a reinforcement layer located on the outer surface of the high temperature resistant copolymer layer and a corrosion resistant polymer protective layer located on the outer surface of the reinforcement layer; the composite gas barrier layer is a multi-layer co-extruded structure, and in order from inside to outside, the composite gas barrier layer comprises a blended modified PVDC layer, a blended modified EVOH layer and a blended modified PA layer; The hierarchical design of the above-mentioned composite material pipeline is set according to the following principles: Gas barrier performance: Through the multi-layer structure of the composite gas barrier layer, the combination of PVDC, EVOH and PA is used to increase the gas barrier effect layer by layer to ensure the effective isolation of hydrogen. High temperature resistance: The high temperature resistant copolymer layer effectively improves the stability of the pipeline in a high temperature environment to avoid softening of the material or degradation of performance due to high temperature. Mechanical strength: The reinforcement layer provides the necessary physical strength to prevent damage to the pipeline caused by external impact or pressure. Corrosion resistance: The corrosion-resistant protective layer ensures the long-term use of the pipeline in harsh environments and avoids corrosion damage. This sequential setting is designed to provide hydrogen leakage protection, high temperature resistance, corrosion resistance and sufficient mechanical strength to ensure the safety and reliability of the pipeline in long-term use.
[0007] The composite gas barrier layer is a crucial part of the composite pipe to prevent hydrogen leakage. Its function is to significantly improve the gas barrier performance of the pipe through the synergistic effect of multiple layers of materials. This design is based on the following key factors: 1. Layer-by-layer enhancement of gas barrier performance: Hydrogen, as a very small and highly diffusive molecule, requires particularly strong materials to effectively block its penetration. The composite gas barrier layer uses a combination of multiple materials to achieve multiple gas barriers. The PVDC layer is located in the innermost layer and mainly plays the core gas barrier role. PVDC has excellent low gas permeability, especially strong resistance to hydrogen penetration, so it is the first line of defense for the composite gas barrier layer. PVDC resin itself can effectively reduce hydrogen leakage, but due to its physical properties (such as brittleness), its mechanical properties usually need to be enhanced. The EVOH layer is located outside the PVDC layer. EVOH has very good gas barrier properties, especially in blocking gases such as hydrogen, oxygen and carbon dioxide. Its main function is to enhance the gas barrier and make up for the shortcomings of the PVDC layer, especially for some smaller gas molecules. The barrier effect is more effective. The structure of EVOH has good polarity, which makes it have higher adsorption and barrier properties for small molecule gases. The modified PA layer (modified polyamide) is located outside the EVOH layer. The addition of the PA layer is to further enhance the mechanical strength between the layers, and its main function is to improve the toughness and impact resistance of the material. PA resin usually has good chemical stability and physical strength, and modification (adding polyvinyl alcohol and nano-montmorillonite) can improve its adaptability to temperature and humidity and gas barrier properties. 2. Synergy of different materials: Each layer of material has its unique performance advantages. The design of the composite material makes full use of the characteristics of different materials so that they can complement each other and play the best effect. Synergy of PVDC and EVOH: Both PVDC and EVOH have excellent gas barrier properties, but PVDC itself is relatively fragile and easy to crack under external impact. In this case, EVOH can play a supporting role and improve the impact resistance of the entire gas barrier layer. By combining PVDC and EVOH layers, their respective advantages can be brought into play, hydrogen penetration can be reduced, and the overall durability of the material can be improved. The modified PA layer not only helps to improve the impact resistance of the material, but also helps to improve the adhesion of the inner and outer layers and prevent separation between the layers. 3. Material processing and durability: interdependence between layers: This layered design not only plays a multiple protective role in gas barrier properties, but also takes into account the processing technology of each layer. PVDC, EVOH and PA layers can be prepared by co-extrusion molding technology, so the complementarity and processing compatibility of materials need to be considered during design. 4. Optimization of design sequence: Arranging the layers of materials in order from the inside to the outside can first block hydrogen with the strongest gas barrier material (PVDC), and then further enhance the barrier effect through the addition of EVOH, and then ensure that the pipeline can be used under high pressure, impact and other conditions through the enhancement and toughness improvement of the PA layer.
[0008] Preferably, nanoclay, PVDC layer toughening agent, PVDC layer crosslinking agent and antioxidant are added to the blended modified PVDC layer. The weight ratio of the materials used is 75-77:3-5:6-8:1-2:0.3-0.5 for PVDC resin: nanoclay: PVDC layer toughening agent: PVDC layer crosslinking agent: antioxidant; the PVDC layer toughening agent is polyethylene or polypropylene, and the PVDC layer crosslinking agent is specifically TBPB. The reasons for adding other materials to the PVDC layer are as follows: Addition of nanoclay: Function: By adding nanoclay to the PVDC layer, the mechanical strength, thermal stability and barrier properties of PVDC can be significantly improved. Nanoclay particles are small in size and have a high surface area, which can fill the tiny pores of the PVDC layer and further reduce the permeation channels of hydrogen. In addition, nanoclay can also improve the impact resistance and toughness of PVDC and prevent the material from breaking under high pressure conditions. Use of toughening agent (polyethylene or polypropylene): The addition of toughening agent helps to improve the toughness of the PVDC layer and reduce its brittleness. Pure PVDC will show brittleness in some extreme environments, resulting in cracking or damage under external forces, thereby reducing its gas-proof performance. Polyethylene or polypropylene as toughening agents have good processability and excellent weather resistance. Their introduction can enhance the flexibility of PVDC and reduce the risk of pipeline rupture at low temperatures or under external forces. Therefore, the use of toughening agents can improve the mechanical properties and durability of the PVDC layer and ensure that the pipeline can withstand the leakage pressure of hydrogen and other gases for a long time. TBPB (tert-ButylPeroxide) is an organic peroxide crosslinking agent that can promote the crosslinking reaction between PVDC molecular chains. The crosslinking agent can form a crosslinking structure between PVDC molecular chains, enhance mechanical strength and barrier properties, and improve the thermal stability, oxidation resistance and mechanical strength of PVDC materials through crosslinking reactions. In composite pipes, crosslinking can make the PVDC layer more stable under high temperature conditions and avoid aging, embrittlement and other problems during long-term use. Especially in high temperature environments, the crosslinking of PVDC molecular chains helps to enhance the stability of its structure, thereby improving the comprehensive performance of composite materials. The use of TBPB crosslinker can ensure that the performance of the PVDC layer remains consistent at high temperatures, further enhancing its anti-aging and anti-degradation capabilities in high-temperature gas transportation. The addition of antioxidants can effectively prevent the PVDC layer from undergoing oxidation reactions during long-term use. Oxidation can lead to a decrease in the performance of the material, especially the gas barrier properties and toughness. Therefore, by adding antioxidants, the long-term stability of the PVDC layer can be improved to ensure the airtightness and structural integrity of the pipeline during long-term use. According to the given material ratio, the formulation of the PVDC layer achieves a balance between the ingredients to ensure the optimization of the material between different properties.The ratio of PVDC resin: nanoclay: toughening agent: crosslinking agent: antioxidant is 75-77:3-5:6-8:1-2:0.3-0.5, which is based on the following considerations: PVDC resin: As the main component, it accounts for the largest proportion and is responsible for providing the basic properties of the PVDC layer, such as gas barrier properties. The selection of a ratio of 75-77% ensures the main structure of the material. Nanoclay: It accounts for a small proportion, but it is very critical to the improvement of gas barrier properties. An appropriate amount of nanoclay can significantly enhance the gas barrier properties and mechanical strength of the PVDC layer, while avoiding material embrittlement or processing difficulties caused by excessive use. Toughening agent and crosslinking agent: An appropriate amount of toughening agent and crosslinking agent can effectively improve the toughness and durability of the material and enhance the pressure resistance of the pipeline. Hydrogen molecules are extremely small and can diffuse through almost all conventional materials. In order to effectively prevent hydrogen leakage, the PVDC layer must have excellent gas barrier properties. By adding the above ingredients (such as nanoclay and crosslinking agent), the structure of the PVDC layer is strengthened and the gas barrier properties are significantly improved.
[0009] Preferably, talcum powder, EVOH layer crosslinker and antioxidant are added to the blended modified EVOH layer, and the materials used are in the weight ratio of EVOH resin: talcum powder: EVOH layer crosslinker: antioxidant 78-82: 7-9: 1.5-2: 0.4-0.6; in the process of preparing the EVOH layer, glycerol is added, and the weight ratio of EVOH resin: glycerol is 100: 3-5; the EVOH layer crosslinker is DCP. By adding glycerol as a plasticizer to the formula, its flexibility can be increased. The addition of glycerol can reduce the brittleness of the EVOH layer, making it less likely to crack or deform when responding to external pressure or ambient temperature changes, which is particularly important for long-term operation of pipelines. Function: Flexibility: Increase the flexibility of the material to avoid cracks and leakage caused by thermal expansion or external force impact. Improve processability: The addition of glycerol also helps to improve the fluidity and molding effect of the EVOH layer during the manufacturing process, making the co-extrusion molding process smoother. The amount of glycerol added needs to be controlled in a lower range to maintain the barrier properties and strength of the EVOH layer. Too much glycerol will reduce the rigidity of the material and affect the gas barrier ability. The amount of 3-5 is to improve flexibility and processability without compromising other properties. The ratio of each material in the EVOH layer (the weight ratio of EVOH resin: talcum powder: EVOH layer crosslinker: antioxidant is 78-82:7-9:1.5-2:0.4-0.6) is set based on the following considerations: 1. EVOH resin: ensure gas barrier performance: EVOH resin is the core material of this layer and is mainly responsible for gas barrier properties, especially hydrogen barrier. The molecular structure of EVOH itself gives it a strong barrier ability to gas. However, the mechanical strength of EVOH resin is relatively weak, and its structural properties need to be enhanced by the addition of other materials. Therefore, EVOH resin occupies a dominant position in this ratio, which ensures the gas barrier performance of the material while avoiding the softness and brittleness problems caused by excessive resin. 2. Talc: Talc, as an inorganic filler, has the function of improving mechanical properties. Its addition can effectively improve the hardness, tensile strength and compressive strength of the EVOH layer. The addition of talcum powder also helps to reduce the cost of EVOH while avoiding over-reliance on high-priced EVOH resin. The amount of talcum powder used is between 7-9, ensuring that the rigidity is enhanced without excessively weakening the flexibility and heat resistance of the material. 3. EVOH layer crosslinker: The reason why the EVOH layer crosslinker is DCP: The use of DCP (diisopropylbenzene peroxide) as a crosslinker in the EVOH layer has a clear purpose: Crosslinking effect: DCP is a typical organic peroxide crosslinker that can form chemical crosslinks between polymer chains through a free radical mechanism. EVOH is a material with good gas barrier properties, but its mechanical strength and heat resistance are relatively limited.Using DCP as a cross-linking agent can establish stronger chemical bonds between the molecular chains of EVOH by initiating a cross-linking reaction, significantly improving the heat resistance, mechanical strength, chemical corrosion resistance and other properties of EVOH. This is crucial for pipelines that prevent hydrogen leakage, because the cross-linked EVOH can maintain gas barrier properties for a longer time, especially in high temperature and long-term use environments. Temperature stability: The cross-linked EVOH layer can still maintain good physical properties under high temperature environments. DCP can effectively initiate a cross-linking reaction at a lower decomposition temperature, which is suitable for matching the processing temperature of EVOH. The cross-linked EVOH can not only withstand higher operating temperatures, but also improve its antioxidant properties. Hydrogen permeability resistance: EVOH itself has good gas barrier properties, but after cross-linking, its molecular structure is more compact, which reduces the permeation rate of hydrogen molecules in the material. Therefore, the use of DCP cross-linking agent is to further improve the effect of preventing hydrogen leakage. The amount of cross-linking agent used in the EVOH layer is between 1.5-2. An appropriate amount of cross-linking agent can improve the stability of the EVOH layer in a long-term high temperature and oxidative environment, but excessive use will increase the brittleness of the material. Therefore, the ratio of 1.5-2 is to achieve a good balance between thermal stability and durability. 4. Antioxidant: In this formula, the ratio of antioxidant in the EVOH layer: The selection of antioxidants needs to be able to effectively prevent oxidation without excessively affecting other properties of the material. The selection of this ratio can effectively inhibit the oxidative degradation of EVOH resin and maintain the stability of the material. By optimizing the ratio of these materials, the EVOH layer of the composite pipe can maintain high-efficiency barrier properties in long-term use, prevent hydrogen leakage, and have good mechanical properties and environmental adaptability.
[0010] Preferably, polyvinyl alcohol, nano-montmorillonite, PA layer plasticizer and antioxidant are added to the blended modified PA layer, and the materials used are in a weight ratio of PA resin: polyvinyl alcohol: nano-montmorillonite: PA layer plasticizer: antioxidant of 100:2.5-3:3-5:1.5-2.5:0.4-0.6; the PA layer plasticizer is TPP. Setting this ratio (PA resin: polyvinyl alcohol: nano-montmorillonite: modified PA layer plasticizer: antioxidant is 100:2.5-3:3-5:1.5-2.5:0.4-0.6) is based on the following considerations: 1. PA resin: basic performance guarantee: PA resin dominates the modified PA layer and is mainly responsible for the basic mechanical properties and gas barrier properties of the layer. Polyamide materials have good toughness and wear resistance, but when facing extreme environments, there are problems such as moisture absorption and insufficient thermal stability. Therefore, the proportion of PA resin is usually set to 100 parts to ensure that its basic role in the entire modified layer is not weakened. 2. Polyvinyl alcohol: Improve processability and water resistance: The role of polyvinyl alcohol in the modified PA layer is to improve its processability, water resistance and hydrogen barrier. PVA is a water-soluble polymer material that can improve the hygroscopicity of polyamide, prevent thermal degradation caused by moisture, and enhance the adhesion and thermal stability of the material. The addition ratio is set to 2.5-3, which can not only improve the performance of the layer, but also avoid excessive addition that causes the material to become brittle. 3. Nano-montmorillonite: Enhance structural properties and thermal stability: Nano-montmorillonite is a layered silicate mineral with a very high specific surface area and good mechanical properties, which can effectively enhance the structural properties of polymers. Its addition can improve the permeability resistance, oxidation resistance and high temperature resistance of the PA layer, and also improve the impact resistance and compressive strength of the composite material. The amount of nano-montmorillonite can ensure the reinforcement effect of the material without introducing too many impurities to affect other properties. 4. Plasticizer: The main function of the plasticizer is to reduce the glass transition temperature (Tg) of the polymer, making the material more flexible and processable. In composite pipes, plasticizers can enhance the mechanical properties and toughness of the modified PA layer, making the pipe more durable, especially in complex working environments where high ductility and crack resistance need to be maintained. TPP (triphenyl phosphate) has special advantages as a plasticizer in polyamide (PA) systems. TPP has a good plasticizing effect. It can effectively reduce the rigidity of the polymer, improve its tensile properties, impact resistance and low-temperature toughness, making the modified PA layer tougher and less likely to crack under stress or low-temperature conditions. TPP's chemical resistance and environmental adaptability: TPP is a more common phosphate plasticizer with good high temperature resistance, chemical stability and anti-aging properties. In composite pipes that prevent hydrogen leakage, TPP can provide enhanced chemical stability, especially under complex environmental conditions, and can effectively prevent the plasticizer from volatilizing or degrading, thereby extending the service life of the pipe.Since hydrogen pipelines may experience extreme chemical environments or temperature changes, the heat resistance and antioxidant properties of TPP can ensure the stability of the modified PA layer in long-term exposure to these environments, maintain its mechanical properties and prevent hydrogen leakage. Low volatility and environmental protection of TPP: In addition to the common performance advantages, low volatility is also one of the outstanding characteristics of triphenyl phosphate as a plasticizer. During the long-term use of the pipeline, the volatility of the plasticizer has an impact on the comprehensive performance of the pipeline. The low volatility of TPP helps to reduce the loss of plasticizers, avoids the polymer embrittlement problem caused by premature volatilization of plasticizers, and enables the pipeline to maintain flexibility and crack resistance for a long time. In addition, TPP has better environmental protection than some traditional plasticizers (such as phthalate plasticizers) and meets the requirements of some environmental regulations. In modern material development, environmental protection and low volatility have become important criteria for material selection. Improve the functionality and processing performance of the PA layer: The use of TPP can also improve the processing of the PA (polyamide) layer, such as reducing the viscosity of the material at high temperature during the manufacturing process, making it easy to form. For high-performance composite pipes, this helps to better control the molding of the material during the production process, obtain excellent interlayer bonding and overall structural stability. Enhance the overall performance of the pipeline: TPP as a plasticizer can improve the toughness and fatigue resistance of the modified PA layer, and reduce the generation and expansion of cracks in stress concentration areas or under long-term cyclic loads. In the application of pipelines to prevent hydrogen leakage, the choice of plasticizer is directly related to the stability and performance retention of the pipeline during long-term use, especially under high pressure and complex temperature changes. The use of plasticizer TPP is to improve the flexibility, chemical resistance, and aging resistance of the modified PA layer, and increase the processability of the material, while extending the service life and stability of the composite pipe. Its low volatility and good environmental performance are also one of the reasons why it is an ideal choice. Antioxidant: Extend service life: The role of antioxidants in the modified PA layer is to prevent oxidative degradation in high temperature environments. Thereby extending the service life of the material. This ratio of antioxidants ensures that the material can maintain good stability during long-term use. Comprehensive analysis: By reasonably setting the proportions of these components, the performance of the modified PA layer is optimized, ensuring that the composite pipe has good hydrogen barrier properties, mechanical strength, corrosion resistance and long-term stability. Specifically: PA resin provides basic mechanical strength and wear resistance. Polyvinyl alcohol improves water resistance and processability, and enhances barrier properties. Nano-montmorillonite enhances the strength, high temperature resistance and permeability of the material. Plasticizers improve the flexibility and processability of the material and avoid brittleness problems. Antioxidants enhance the thermal oxidation resistance of the material and extend its service life. Through this ratio design, the modified PA layer can provide a good gas barrier effect in hydrogen leakage-proof pipelines, while having sufficient mechanical strength and long-term durability.
[0011] Preferably, the composite material used in the reinforcement layer is prepared by vacuum-assisted resin transfer molding, and the materials used are in a weight ratio of carbon fiber: epoxy resin: amorphous nano-silica of 60-70:30-40:5-8. The reinforcement layer is prepared by vacuum-assisted resin transfer molding, and the choice of setting the ratio has its own unique engineering design and performance requirements. 1. Why vacuum-assisted resin transfer molding is used to prepare the reinforcement layer: Vacuum-assisted resin transfer molding is a molding process used in composite material manufacturing. There are several key reasons for choosing this method: Improve the density and structural strength of the composite material: The VARTM process places a dry fiber preformed structure in a mold and guides the resin into the fiber by vacuum suction, which helps to efficiently fill the gaps between the fibers and ensure uniform distribution of the resin. This method can achieve a higher fiber volume ratio, thereby improving the strength, stiffness and impact resistance of the reinforcement layer. Reduce bubbles and uneven distribution of resin: The auxiliary effect of the vacuum helps to eliminate possible bubbles or uneven resin distribution, improve the density and reliability of the composite material, and avoid the generation of weaknesses. This is particularly important for structures such as pipelines that are subject to pressure and stress, especially in applications to prevent hydrogen leakage, where the airtightness and strength of the material are crucial. Suitable for the combination of high-performance materials: Provide better fiber / resin bonding, thereby enhancing the mechanical properties, corrosion resistance, etc. of the composite material. 2. Set the ratio of carbon fiber, epoxy resin and amorphous nano-silica as follows: The ratio of carbon fiber is high (60-70): Strengthen the mechanical properties of the material: Carbon fiber, as a high-strength and high-rigidity reinforcement material, can greatly improve the tensile strength, compressive strength and bending resistance of the composite material. The reinforcement layer needs to bear pressure and external stress, so a high ratio of carbon fiber can provide sufficient mechanical properties to ensure the structural integrity and deformation resistance of the pipeline. Improve thermal conductivity: The thermal conductivity of carbon fiber can also help the composite material dissipate heat better in a high-temperature environment to avoid local overheating or thermal deformation. The ratio of epoxy resin is low (30-40): The role of the resin is to bond and solidify the fiber: Epoxy resin not only acts as a binder to bind the carbon fibers together, but also plays a curing role to ensure the structural stability of the entire reinforcement layer. The relatively low proportion of epoxy resin is because the resin mainly plays a fixing and filling role, and too much resin will increase the weight of the material and reduce the mechanical properties. High temperature and chemical resistance of the resin: Epoxy resin has good high temperature resistance and corrosion resistance. While strengthening the composite material, it can adapt to the requirements of high temperature and chemical corrosion environment. The proportion of amorphous nano-silica is low (5-8): Enhanced resin performance: The addition of amorphous nano-silica is intended to improve the mechanical properties, thermal stability and wear resistance of the resin. Nano-silica has a strong reinforcing effect and can fill the tiny gaps in epoxy resin, improving its compressive strength, shear strength and heat resistance.Improve fluidity and curing process: Nano-silica can improve the fluidity of the resin, making it more uniform when injected into the mold, thereby improving the quality of the finished product. 3. Summary of the purpose of proportion selection: Balance of comprehensive performance: A high proportion of carbon fiber provides strength, stiffness and thermal conductivity, suitable for withstanding high pressure, avoiding deformation and crack expansion. Epoxy resin plays the role of connecting and fixing carbon fibers, but the proportion is relatively low to avoid excessive resin reducing the overall mechanical properties. The appropriate use of amorphous nano-silica enhances the high temperature resistance and corrosion resistance of the resin, while also improving the stability and processability of the overall material. Performance requirements for hydrogen leakage prevention: The reinforcement layer of the composite material can provide excellent mechanical properties, air tightness, high temperature resistance and corrosion resistance through this optimized ratio combination, thereby meeting the special requirements for hydrogen leakage prevention. Through vacuum-assisted resin transfer molding, the high strength, uniformity and durability of the composite material can be ensured. In the proportion design of the reinforcement layer, the selection and proportion of carbon fiber, epoxy resin and nano-silica are based on the comprehensive performance requirements of the materials, aiming to maximize their mechanical properties, heat resistance, corrosion resistance and processing performance, ensuring that the pipeline can effectively prevent hydrogen leakage and maintain long-term stability in harsh environments.
[0012] Preferably, the material of the inner pipe layer is one of RTP and TCP. The selection of one of the reinforced thermoplastic pipe (RTP) and thermoplastic composite pipe (TCP) as the inner pipe layer is mainly based on the following comprehensive performance requirements and material property analysis: 1. Excellent gas barrier performance: Requirement: Preventing hydrogen permeation is the key goal. As the first barrier, the inner tube layer needs to have extremely low permeability to hydrogen. Advantages of RTP / TCP: Both RTP and TCP have low gas permeability, especially when combined with reinforced fibers and multi-layer composite design in the structure, the possibility of hydrogen leakage can be significantly reduced. 2. Mechanical strength and pressure resistance performance requirements: Hydrogen transportation is usually carried out under high pressure, requiring the inner tube layer to have sufficient mechanical strength, deformation resistance and high pressure resistance. RTP / TCP can withstand high working pressure. 3. Chemical corrosion resistance: Requirement: Hydrogen transportation pipelines need to face certain chemical corrosion environments, requiring the inner tube layer material to be stable and corrosion-resistant. Thermoplastic matrix materials themselves have good chemical corrosion resistance and can resist hydrogen erosion during long-term use. Thermoplastic composites used in TCP also have excellent acid and alkali resistance and chemical stability, and are particularly suitable for complex chemical environments. 4. Temperature adaptability: Requirement: Pipelines may operate in high or low temperature environments, and materials need to adapt to changes in temperature differences without failure. Advantages of RTP / TCP: RTP can adapt to a wider temperature range. The base material of TCP performs better in high temperature stability and can be used for a long time under harsh high temperature conditions. 5. Manufacturability and economy: Requirements: The material needs to be easy to process and have an acceptable cost. Advantages of RTP / TCP: RTP uses a thermoplastic matrix, the manufacturing process is relatively simple, and the cost is low, which is suitable for large-scale industrial applications. The manufacturing process of TCP is more complicated, but its high performance makes it more cost-effective under more demanding conditions (such as high pressure and large flow hydrogen transportation). 6. Compatibility with composite gas barrier layer: Requirements: The inner pipe layer and the composite gas barrier layer (PVDC, EVOH, PA, etc.) need to have good interface bonding to ensure the integrity and durability of the composite pipeline. Comprehensive analysis: Comprehensive performance: RTP and TCP have both high strength, low permeability, chemical corrosion resistance and good temperature adaptability. Mature technology: The manufacturing technology of RTP and TCP has been widely used in high-pressure oil and gas transportation with high reliability. Economic feasibility: RTP is more suitable for large-scale, standard application scenarios, while TCP is suitable for high-end scenarios with more stringent performance requirements. Recommended application scenarios: RTP (reinforced thermoplastic pipe): suitable for medium and low pressure hydrogen transportation, or in cost-sensitive projects. TCP (thermoplastic composite pipe): suitable for hydrogen transportation under high pressure or extreme environments, especially under high temperature or corrosive conditions.
[0013] Preferably, the material used for the high temperature resistant copolymer layer is polyimide. Polyimide can maintain stable performance at very high temperatures, and can generally withstand a temperature range of -200°C to 400°C. This high temperature stability makes it an ideal material for handling high temperature environments, especially for pipeline systems with large temperature changes. Mechanical strength and toughness: Polyimide has excellent tensile strength, hardness and impact resistance, which can effectively prevent the deformation and breakage of pipelines in high temperature environments. Chemical stability: Polyimide has very strong corrosion resistance to most chemicals (including strong acids, strong alkalis, solvents, etc.) and can be used for a long time in harsh chemical environments. This is crucial for anti-hydrogen leakage pipelines, because hydrogen and certain corrosive substances may come into contact with the pipeline, requiring the pipeline material to have strong corrosion resistance. Electrical properties: Polyimide has good electrical insulation properties. Polyimide has extremely high temperature resistance and good chemical stability. As a high temperature resistant copolymer layer material, polyimide can effectively protect composite pipes from damage due to thermal expansion and contraction in high temperature environments, and can also effectively prevent the leakage of corrosive substances such as hydrogen. In the design of composite pipes to prevent hydrogen leakage, polyimide can provide the necessary temperature resistance and chemical corrosion resistance to ensure the long-term reliability of the pipe. It has good processing performance and can be smoothly formed and processed during the pipe manufacturing process to meet the requirements of complex pipe design.
[0014] Preferably, the material used for the corrosion-resistant polymer protective layer is polytetrafluoroethylene or fluorinated ethylene-propylene copolymer. In the composite pipe for preventing hydrogen leakage, polytetrafluoroethylene (PTFE) or fluorinated ethylene-propylene copolymer (FEP) is selected as the material of the corrosion-resistant polymer protective layer, mainly based on their excellent chemical stability and corrosion resistance. The following is a detailed analysis of the reasons: Polytetrafluoroethylene: Main features: Excellent corrosion resistance: PTFE is almost completely chemically inert and has strong tolerance to most corrosive substances such as acids, alkalis, salt solutions, solvents and oxidizing gases. PTFE has a low friction coefficient, which can effectively reduce friction and wear, and is suitable for application scenarios with fluid flow in the pipeline system. Aging resistance and stability: PTFE is not easily aged by environmental factors such as ultraviolet rays and oxidation, and can be used stably for a long time. Hydrogen has strong permeability and reactivity. The extremely high chemical stability and corrosion resistance of PTFE enable it to effectively prevent hydrogen from reacting or leaking with the pipeline surface. In addition, the high temperature resistance and oxidation resistance of PTFE make it an ideal choice for maintaining performance in high temperature environments, especially in the protective layer of pipelines to prevent hydrogen leakage. Fluorinated ethylene-propylene copolymer (FEP): Made from ethylene and tetrafluoroethylene, it has similar properties to PTFE, but is relatively easier to process and mold. Main features: Excellent chemical stability: FEP has strong corrosion resistance to most chemicals, especially acids, alkalis, solvents and hydrogen, and can effectively prevent hydrogen penetration or leakage. Compared with PTFE, FEP has better processing performance and can be processed by traditional thermoplastic molding methods (such as injection molding, extrusion, etc.), which is of great significance for the large-scale production of hydrogen leakage-proof pipes. Transparency: FEP has good transparency, which may provide additional visual inspection convenience in some applications, especially in pipeline monitoring systems. FEP is similar to PTFE in corrosion resistance and high temperature resistance, and has excellent processing properties, making it a favorable choice in pipeline protective layers. The selection of PTFE or FEP as the material for the corrosion-resistant polymer protective layer is based on the following points: Corrosion resistance: The reactivity of hydrogen requires the pipeline material to have strong chemical stability, especially in a highly corrosive environment. Both PTFE and FEP can provide strong corrosion resistance, ensuring that hydrogen does not penetrate or react with the pipeline. High temperature resistance: Hydrogen pipelines may face high temperature environments in industry, which requires the pipeline protective layer to have high temperature stability. PTFE has very strong high temperature resistance, and FEP can also meet the temperature requirements in most industrial applications. Processability: FEP has better processability and is easier to process and shape than PTFE, especially in pipeline protective layers that require complex shapes. Long-term stability: Both PTFE and FEP have anti-oxidation and anti-aging properties, and can maintain excellent performance during long-term use to prevent the pipeline protective layer from degrading due to environmental factors.Therefore, choosing PTFE or FEP as the corrosion-resistant protective layer can ensure the reliability and stability of the pipeline during long-term use, especially providing the necessary protection in high temperature and hydrogen leakage environments to ensure the best anti-leakage effect.
[0015] Preferably, the reinforcing layer adopts a multi-layer interwoven fiber structure, the laying direction of each layer of fiber is 0° / 90° or ±45°, the number of layers is 3-7 layers, and at least one layer adopts ±45°; the reinforcing layer adopts a temperature-controlled curing box during the curing process, and the temperature in the curing box is set to 130°C to 150°C; a modified polyamine curing agent is selected as the curing agent for the epoxy resin, and the curing time is 2-4 hours.
[0016] 1. The necessity of multi-layer interwoven fiber structure: This design ensures that the pipeline has sufficient tensile strength, shear strength and impact resistance. Laying direction of multi-layer interwoven fibers: 0° / 90° laying: The fibers in the 0° direction provide axial strength, so that the pipeline is not easily stretched and deformed under the internal pressure of hydrogen. The fibers in the 90° direction provide circumferential strength to avoid annular cracking or deformation caused by internal pressure. ±45° laying: The fibers in the ±45° direction increase the shear strength of the pipeline and improve the torsional performance, which can cope with bending, lateral loads or complex external forces. The ±45° layer can also effectively disperse local stress and prevent stress concentration from causing structural damage. 3-7 layers: The multi-layer structure can significantly improve the overall rigidity and strength of the composite material, making the pipeline suitable for high-pressure hydrogen transmission needs while controlling material cost and weight. At least one layer of ±45°: By adding a fiber layer in the ±45° direction, the strength limitations of the 0° / 90° laying can be compensated, and the overall stability of the pipeline under multi-directional stress conditions can be improved.
[0017] 2. Setting of curing process: The temperature of the temperature-controlled curing box is set to 130℃ to 150℃. The curing temperature is the key parameter of the epoxy resin curing reaction. Too low temperature: The curing rate is slow, resulting in incomplete curing of the material, reducing the mechanical properties and durability. Too high temperature: Inducing thermal stress or causing poor bonding between the reinforcing fiber / resin interface. 130℃ to 150℃: This temperature range is the commonly used optimized temperature range in the epoxy resin system, which can ensure that the reinforcement layer is fully cured, thereby maximizing the mechanical properties and high temperature resistance. Select modified polyamine curing agent as epoxy resin curing agent: Advantages of modified polyamine: Moderate reaction speed: It can provide a suitable curing rate in the range of 130℃ to 150℃ to ensure uniform curing of the internal structure of the composite material. High toughness: The modified polyamine curing agent can give the cured epoxy resin higher toughness and impact resistance, making the pipeline reinforcement layer more durable. Heat aging resistance: The epoxy resin cured by modified polyamine can withstand higher temperatures and improve the thermal stability of the pipeline. The curing time is set to 2-4 hours: The curing time needs to find a balance between strength growth and production efficiency. Too short time: The curing may not be complete, affecting the mechanical properties and structural stability of the reinforcement layer. Too long time: It will reduce production efficiency and increase manufacturing costs. 2-4 hours: Under a temperature-controlled environment of 130°C to 150°C, 2-4 hours can achieve complete curing of the epoxy resin, ensuring that the reinforcement layer achieves ideal mechanical properties and thermal stability. The purpose of the above settings is to optimize the structure and processing technology of the reinforcement layer so that it has the following properties: High strength and pressure resistance: The multi-layer fiber interwoven structure enables the reinforcement layer to withstand the internal and external pressure of the hydrogen pipeline. Shear and torsion resistance: ±45° plying significantly improves the stability of the reinforcement layer under complex stress conditions. Thermal stability and chemical stability: Through temperature-controlled curing process and modified polyamine curing agent, it is ensured that the reinforcement layer can operate stably for a long time in high temperature and corrosive environments. Efficient production and reliability: Reasonable curing time and temperature settings improve production efficiency while ensuring performance. The above parameters are set to strike a balance between mechanical properties, thermal properties and production efficiency, ensuring that the reinforcement layer of the composite pipe can meet the high strength, high stability and long life requirements required for hydrogen transmission, while making the production process feasible and economical. These design details are crucial to the safety and reliability of hydrogen pipelines.
[0018] The parameters of the carbon fiber used are as follows: Type: Use long fibers or continuous fibers with high strength and low density to improve the tensile strength and rigidity of the pipe. Fiber diameter: 5-10μm; Tensile strength: 3000-7000 MPa; Modulus: 200-800 GPa Preferably, the antioxidant used is Irganox 1010 antioxidant or BHT antioxidant.
[0019] The present invention proposes a composite material pipeline that prevents hydrogen leakage. Its structural design integrates functional materials at multiple levels to cope with various challenges faced by hydrogen pipelines, especially hydrogen leakage problems. The following are the beneficial effects of the present invention: 1. Effectively prevent hydrogen leakage: The multi-layer structural design of the inner tube layer, composite gas barrier layer, high temperature resistant copolymer layer, reinforcement layer and corrosion resistant polymer protective layer of the composite material pipeline can effectively isolate the contact between hydrogen and the external environment, reduce the penetration and leakage of hydrogen, ensure the air tightness of the pipeline for a long time, and meet the safety requirements of high-pressure hydrogen transportation. In particular, the composite gas barrier layer uses a multi-layer co-extrusion molding structure, which is composed of a modified PVDC layer, an EVOH layer and a PA layer in sequence. The interaction of the three layers of materials greatly enhances the gas barrier effect.
[0020] 2. Improve pipeline strength and high temperature resistance: In high temperature environments, the high temperature resistant copolymer layer (polyimide) of the pipeline can effectively resist the damage of the thermal environment to the pipeline material and extend the service life of the pipeline. The reinforcement layer is prepared by vacuum assisted resin transfer molding (VARTM) method, combined with a composite material of carbon fiber, epoxy resin and nano-silicon dioxide, which significantly enhances the strength and pressure resistance of the pipeline, enabling it to operate stably for a long time under high pressure and harsh environment.
[0021] 3. Reduce the risk of hydrogen embrittlement and corrosion: Traditional steel pipes are prone to hydrogen embrittlement in high-pressure hydrogen environments, leading to cracking and failure of the pipes. The composite pipes in the present invention use a corrosion-resistant polymer protective layer (such as polytetrafluoroethylene or fluorinated ethylene-propylene copolymer), which can effectively prevent erosion by corrosive media and avoid failure of metal materials due to corrosion or hydrogen embrittlement.
[0022] 4. Improve the flexibility and operability of the pipeline: Composite material pipelines are more flexible and adaptable than traditional steel pipes. They can be manufactured in the form of long strips or coils, which are easy to transport, lay and install. This design helps to simplify the construction process of hydrogen pipelines, reduce labor and equipment costs during construction, and improve construction efficiency.
[0023] 5. Reduce pipeline weight and save material costs: Composite pipes are lighter than traditional steel pipes and have lower material costs. By using lightweight plastic materials such as polyethylene and polyvinyl chloride, combined with high-strength composite materials, it not only reduces production and transportation costs, but also ensures the safety and long-term stability of the pipeline in high-pressure hydrogen transportation.
[0024] 6. Material optimization to improve anti-oxidation and anti-aging properties: Antioxidants and cross-linking agents are added to the composite materials to improve the anti-oxidation and anti-aging properties of the pipeline materials, prevent material degradation caused by oxidation, thereby extending the service life of the pipeline and ensuring that it will not leak due to aging, oxidation and other problems during long-term use.
[0025] 7. Strong adaptability to meet different hydrogen transportation needs: The composite material pipeline of the present invention can flexibly select the inner pipe layer material (such as RTP and TCP) according to the requirements of specific applications, and adapt to different hydrogen transportation environments. It can not only meet the conventional low-pressure hydrogen transportation needs, but also cope with transportation tasks under higher pressure or high temperature environments, and has a wide range of applicability.
[0026] 8. Optimized design of the reinforcement layer structure: The reinforcement layer adopts a multi-layer interwoven fiber structure and a temperature-controlled curing process to ensure the strength and stability of the pipeline under pressure and temperature changes. The fiber layout in different directions (such as 0° / 90° or ±45°) enhances the tensile strength and compressive resistance of the pipeline, ensuring good performance in complex environments.
[0027] In summary, the hydrogen leakage prevention composite material pipeline of the present invention, by virtue of its multi-layer composite structure, excellent material selection and optimized production process, has the characteristics of excellent gas barrier performance, high strength, corrosion resistance, high temperature resistance and good flexibility. It can effectively solve the hydrogen embrittlement, leakage and corrosion problems faced by traditional steel pipes in the hydrogen transmission process, and has significant technical advantages and broad application prospects. DETAILED DESCRIPTION
[0028] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments. Specific embodiments
[0029] A composite material pipeline for preventing hydrogen leakage, the composite material pipeline comprises an inner tube layer, a composite gas barrier layer located on the outer surface of the inner tube layer, a high temperature resistant copolymer layer located on the outer surface of the composite gas barrier layer, a reinforcement layer located on the outer surface of the high temperature resistant copolymer layer, and a corrosion resistant polymer protective layer located on the outer surface of the reinforcement layer; the composite gas barrier layer is a multi-layer co-extrusion molding structure, and in order from inside to outside, the composite gas barrier layer comprises a blended modified PVDC layer, a blended modified EVOH layer and a blended modified PA layer. The thickness parameters are as follows: inner tube layer: 3.0 mm, high temperature resistant copolymer layer: 0.3 mm, reinforcement layer: 2.0 mm, corrosion resistant polymer protective layer: 0.3 mm.
[0030] In the blended modified PVDC layer, nanoclay, PVDC layer toughening agent, PVDC layer crosslinking agent and antioxidant are added, and the materials used are in a weight ratio of PVDC resin: nanoclay: PVDC layer toughening agent: PVDC layer crosslinking agent: antioxidant of 76:4:7:1.5:0.4; the PVDC layer toughening agent is polyethylene, and the PVDC layer crosslinking agent is specifically TBPB.
[0031] In the blended modified EVOH layer, talcum powder, EVOH layer crosslinking agent and antioxidant are added, and the materials used are in a weight ratio of EVOH resin: talcum powder: EVOH layer crosslinking agent: antioxidant 80:8:1.8:0.5; in the process of preparing the EVOH layer, glycerol is added, and the weight ratio of EVOH resin: glycerol is 100:4; the EVOH layer crosslinking agent is DCP.
[0032] In the blended modified PA layer, polyvinyl alcohol, nano-montmorillonite, PA layer plasticizer and antioxidant are added, and the materials used are in a weight ratio of PA resin: polyvinyl alcohol: nano-montmorillonite: PA layer plasticizer: antioxidant of 100:3:4:2:0.5; the PA layer plasticizer is TPP.
[0033] During the coextrusion process, the binder is squeezed between the layers to ensure good adhesion between each layer.
[0034] The reinforcement layer is prepared by vacuum assisted resin transfer molding, and the materials used are in a weight ratio of 70:35:6 for carbon fiber:epoxy resin:amorphous nano-silica. The reinforcement layer adopts a multi-layer interwoven fiber structure, and the laying direction of each layer of fiber is 0° / 90° and ±45°. The number of layers is 5, and two layers are ±45°; the specific process is as follows: Preparation: Cleaning and surface treatment: Make sure that there is no dust, oil or other pollutants on the surface of the high-temperature copolymer layer. It can be wiped with industrial cleaners and the surface is lightly polished (such as using fine sandpaper) to increase the surface roughness and enhance the bonding performance. After cleaning, use high-purity ethanol or acetone for secondary cleaning to completely remove the residue. Adhesive coating: Use an adhesive compatible with epoxy resin and evenly apply a layer of adhesive on the surface of the high-temperature copolymer layer. The function of the adhesive is to enhance the adhesion between the high-temperature copolymer layer and the reinforcement layer. Let the adhesive stand until the surface becomes slightly sticky (usually 15-30 minutes). 2. Preparation of reinforcement layer: The reinforcement layer is directly molded on the outer surface of the copolymer layer by vacuum assisted resin transfer molding (VARTM) process. 2.1 Carbon fiber layer laying: Selection of carbon fiber material: According to the design, high-strength carbon fiber fabric is selected, and a multi-layer interlaced structure is adopted. The laying direction is 0° / 90° and ±45°, with a total of 5 layers, of which the middle two layers are ±45°. Laying carbon fiber layer: The first layer of carbon fiber is laid directly on the surface of the high-temperature resistant copolymer layer, and the subsequent layers are laid in sequence. When laying each layer, ensure that the carbon fiber fabric is flat and wrinkle-free, and avoid air inclusion. 2.2 Resin mixing and injection: Resin preparation: According to the weight ratio of epoxy resin: amorphous nano-silica = 35:6, amorphous nano-silica is dispersed in epoxy resin and stirred evenly. Add modified polyamine curing agent, stir thoroughly and perform vacuum degassing to remove bubbles generated during mixing. Vacuum assisted injection: Cover the surface of the laid carbon fiber layer with separation membrane, guide net and vacuum bag membrane. Use sealing strips to seal the vacuum environment and connect the vacuum pump and resin injection device through pipes. Set the vacuum pressure to -0.8 to -0.9 bar, and inject the epoxy resin into the carbon fiber layer at an injection pressure of 0.1-0.2 MPa to allow it to fully penetrate. 2.3 Curing treatment: Curing: While the vacuum bag remains closed, place the entire pipeline in a temperature-controlled curing box, set the curing temperature to 140°C, and the curing time to 3 hours. Notes: Adhesive selection and coating: Use an adhesive that is compatible with the epoxy resin and copolymer layer, such as an amine-containing adhesive or an epoxy-modified adhesive, to ensure a firm bond between the layers. Vacuum process quality control: Ensure that the vacuum bag is well sealed and no bubbles remain during the injection process to prevent gaps or insufficient strength in the reinforcement layer.
[0035] The material of the inner tube layer is a reinforced thermoplastic plastic tube, the material used for the high temperature resistant copolymer layer is polyimide, and the material used for the corrosion resistant polymer protective layer is polytetrafluoroethylene.
[0036] Connection between the inner tube layer and the composite gas barrier layer: Connection method: The connection between the inner tube layer and the composite gas barrier layer (blended modified PVDC layer) is completed by welding or bonding process. Since the composite gas barrier layer is usually multi-layer co-extrusion (PVDC, EVOH, PA co-extrusion), they can form a tight bonding interface on the surface of the inner tube layer to ensure seamless connection.
[0037] Connection between the composite gas barrier layer and the high temperature resistant copolymer layer: Connection method: When the composite gas barrier layer (blended modified PA layer) and the high temperature resistant copolymer layer (polyimide) are connected, the surface will be pretreated first to enhance the interface adhesion. Polyimide has excellent performance at high temperatures, so it plays a protective role in the high temperature environment of the pipeline. Then it is combined with the gas barrier layer by bonding.
[0038] Connection between the reinforcement layer and the corrosion-resistant polymer protective layer: Connection method: The reinforcement layer and the corrosion-resistant protective layer are connected by chemical bonding or hot melt bonding. The reinforcement layer is combined with the welding process or adhesive bonding technology to ensure that the pipeline does not leak in harsh chemical environments.
[0039] In the preparation process of the composite gas barrier layer, the preparation parameters are as shown in Table 1: ;
[0040] Performance test, as shown in Table 2: ;
[0041] Analysis of test results: Hydrogen permeability: Test method: According to ASTM D1434, the permeation rate of hydrogen in the pipeline material is tested to evaluate the air tightness of the pipeline. The PVDC, EVOH, and PA layers in the composite material are the main gas barrier materials, and their permeabilities need to be very low to effectively prevent hydrogen leakage. Analysis: The multi-layer structure of the composite gas barrier layer, especially the nano-modification and enhanced gas barrier ability of the PVDC layer, should be able to significantly reduce the permeability of hydrogen.
[0042] High temperature stability: Test method: Thermogravimetric analysis (TGA) is used to determine the thermal decomposition temperature of composite materials at high temperatures. Polyimide can maintain its stability at high temperatures, so high temperature resistance is particularly critical. Analysis: The high temperature resistant copolymer layer (polyimide) has good thermal stability and effectively protects the pipeline from material degradation in high temperature environments.
[0043] Corrosion resistance: Test method: The corrosion resistance of polytetrafluoroethylene (PTFE) is evaluated by simulating the corrosive environment through salt spray test. Analysis: The use of corrosion-resistant protective layer (PTFE) should be able to effectively prevent the damage of pipelines in corrosive environments, especially in harsh chemical or wet environments.
[0044] Wear resistance: Test method: Use Taber abrasion test to evaluate the wear resistance of the reinforcement layer. Analysis: Through the reinforcement layer of carbon fiber reinforced epoxy resin, the pipeline surface has high wear resistance, which can reduce the loss in long-term use and increase the service life of the pipeline.
[0045] Compression and Tensile Strength: Test Method: Compression test and tensile test are used to check the performance of the inner tube layer and reinforcement layer under high pressure and tension. Analysis: The inner tube layer is made of reinforced thermoplastics, combined with the carbon fiber epoxy resin structure of the reinforcement layer, which can maintain good structural strength under high pressure and high tension environment.
[0046] Temperature resistance: Test method: Evaluate the stability of materials under high temperature conditions through heat deformation temperature test.
[0047] Analysis: The temperature resistance of the inner tube layer and the high temperature resistant copolymer layer can meet the requirements of long-term use in high temperature environment. Oxidation resistance: Test method: The oxidation induction time (OIT) test is used to evaluate the stability of the material in an oxidizing environment. Analysis: Especially the materials of the composite gas barrier layer and the reinforcement layer have good oxidation resistance, which prolongs the service life and avoids oxidative degradation.
[0048] Hydrogen leakage test: Test method: Detect hydrogen leakage in the pipeline to ensure the sealing of the pipeline in a high-pressure hydrogen environment. Analysis: The multi-layer structure of the composite gas barrier layer, especially the blending modification of PVDC and EVOH, should effectively prevent hydrogen leakage.
[0049] Dimensional stability: Test method: Test the dimensional changes of materials under high temperature or high humidity environment. Analysis: Composite materials should maintain dimensional stability to avoid deformation of pipes due to thermal expansion and contraction or environmental changes.
[0050] Summary: The composite pipe is designed with multiple properties such as efficient hydrogen leakage protection, high temperature resistance, corrosion resistance, and wear resistance through multi-layer structure and fine material selection, ensuring the long-term stability of the pipe in various complex environments. The efficient synergy of materials at all levels (such as composite gas barrier layer, reinforcement layer, and protective layer) has shown excellent indicators in performance testing and is suitable for use in situations where hydrogen leakage needs to be prevented.
[0051] The specific embodiments described herein are merely examples of the spirit of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the described specific embodiments or replace them in a similar manner, but will not deviate from the spirit of the present invention or exceed the defined scope. Specifically, the present invention encompasses other embodiments with any combination of features from the above-mentioned different embodiments. With respect to the use of the expression "generally" or "substantially", this patent application should be understood to disclose that these features and values are also fully satisfied, i.e., there is no aforementioned characterization as "generally" or "substantially".
Claims
1. A composite material pipeline for preventing hydrogen leakage, characterized in that: The composite material pipeline includes an inner tube layer, a composite gas barrier layer located on the outer surface of the inner tube layer, a high temperature resistant copolymer layer located on the outer surface of the composite gas barrier layer, a reinforcement layer located on the outer surface of the high temperature resistant copolymer layer and a corrosion resistant polymer protective layer located on the outer surface of the reinforcement layer; the composite gas barrier layer is a multi-layer co-extrusion molding structure, and in order from inside to outside, the composite gas barrier layer includes a blended modified PVDC layer, a blended modified EVOH layer and a blended modified PA layer.
2. The composite material pipeline for preventing hydrogen leakage according to claim 1, characterized in that: In the blended modified PVDC layer, nanoclay, PVDC layer toughening agent, PVDC layer crosslinking agent and antioxidant are added, and the materials used are in a weight ratio of PVDC resin: nanoclay: PVDC layer toughening agent: PVDC layer crosslinking agent: antioxidant of 75-77:3-5:6-8:1-2:0.3-0.5; the PVDC layer toughening agent is polyethylene or polypropylene, and the PVDC layer crosslinking agent is specifically TBPB.
3. The composite material pipeline for preventing hydrogen leakage according to claim 1, characterized in that: In the blended modified EVOH layer, talcum powder, EVOH layer crosslinking agent and antioxidant are added, and the materials used are in a weight ratio of EVOH resin: talcum powder: EVOH layer crosslinking agent: antioxidant 78-82:7-9:1.5-2:0.4-0.6; in the process of preparing the EVOH layer, glycerol is added, and the weight ratio of EVOH resin: glycerol is 100:3-5; the EVOH layer crosslinking agent is DCP.
4. The composite material pipeline for preventing hydrogen leakage according to claim 1, characterized in that: In the blended modified PA layer, polyvinyl alcohol, nano-montmorillonite, PA layer plasticizer and antioxidant are added, and the materials used are in a weight ratio of PA resin: polyvinyl alcohol: nano-montmorillonite: PA layer plasticizer: antioxidant of 100:2.5-3:3-5:1.5-2.5:0.4-0.6; the PA layer plasticizer is TPP.
5. The composite material pipeline for preventing hydrogen leakage according to claim 1, characterized in that: The reinforcing layer is prepared by a vacuum assisted resin transfer molding method, and the materials used are carbon fiber: epoxy resin: amorphous nano-silicon dioxide in a weight ratio of 60-70:30-40:5-8.
6. The composite material pipeline for preventing hydrogen leakage according to claim 1, characterized in that: The material of the inner pipe layer is one of RTP and TCP.
7. The composite material pipeline for preventing hydrogen leakage as claimed in claim 1, characterized in that: The material used for the high temperature resistant copolymer layer is polyimide.
8. The composite material pipeline for preventing hydrogen leakage as claimed in claim 1, characterized in that: The material used for the corrosion-resistant polymer protective layer is polytetrafluoroethylene or fluorinated ethylene-propylene copolymer.
9. The composite material pipeline for preventing hydrogen leakage according to claim 1, characterized in that: The reinforcing layer adopts a multi-layer interwoven fiber structure, the laying direction of each layer of fiber is 0° / 90° or ±45°, the number of layers is 3-7, and at least one layer adopts ±45°; the reinforcing layer adopts a temperature-controlled curing box during the curing process, and the temperature in the curing box is set to 130°C to 150°C; a modified polyamine curing agent is selected as the curing agent for the epoxy resin, and the curing time is 2-4 hours.
Citation Information
Patent Citations
Fiber reinforced thermoplastic composite material hydrogen conveying pipeline and manufacturing method thereof
CN117698211A
High-performance composite pipeline for transporting hydrogen and preparation method of high-performance composite pipeline
CN118309848A
Intelligent thermoplastic composite material hydrogen conveying pipeline and preparation method thereof
CN118361600A
Silica gel hose resistant to strong acid, strong alkali and corrosion
CN222164082U
Saponified ethylene-vinyl ester copolymer resin composition, resin tube for high-pressure gas or resin liner for composite container, and high-pressure gas hose or composite container
US20180016430A1